Global research landscape and trends of papillary thyroid cancer therapy: a bibliometric analysis - Song, Bo; Lin, Zheyu; Feng, Chuyao; Zhao, Xu; Teng, Weiping (Frontiers in Endocrinology, 2023)
Papillary Thyroid cancer (PTC); Web of Scientific Core Collection (WoSCC); Thyroid cancer (TC); Web of Science (WoS); Journal Citation Reports (JCR); Journal of Clinical Endocrinology and Metabolism (J CLIN ENDOCR METAB); log-likelihood ratio (LLR); prophylactic central neck dissection (pCND); total thyroidectomy (TT); locoregional recurrence (LRR); Radioactive iodine (RAI); RAI-resistant differentiated thyroid cancer (RAIR-DTC); thyroid-stimulating hormone (TSH); active surveillance (AS); Thermal ablation (TA); radiofrequency ablation (RFA); laser ablation (LA); microwave ablation (MWA); B-type RAF kinase (BRAF)